2022
DOI: 10.1111/jdi.13864
|View full text |Cite
|
Sign up to set email alerts
|

Progressive loss of corneal nerve fibers is associated with physical inactivity and glucose lowering medication associated with weight gain in type 2 diabetes

Abstract: Aims/Introduction: Limited studies have identified risk factors linked to the progression of diabetic peripheral neuropathy (DPN) in type 2 diabetes. This study examined the association of risk factors with change in neuropathy measures over 2 years. Materials and Methods: Participants with type 2 diabetes (n = 78) and controls (n = 26) underwent assessment of clinical and metabolic parameters and neuropathy using corneal confocal microscopy (CCM), vibration perception threshold (VPT), and the DN4 questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Regular exercise not only improves blood glucose levels but also reduces cardiovascular risk factors and contributes to weight loss. Moreover, physical activity also demonstrated the benefits for diabetic neuropathy in a previous study 22 . In that study, type 2 diabetes mellitus was associated with neuropathy and a progressive loss of corneal nerve fibers.…”
supporting
confidence: 53%
“…Regular exercise not only improves blood glucose levels but also reduces cardiovascular risk factors and contributes to weight loss. Moreover, physical activity also demonstrated the benefits for diabetic neuropathy in a previous study 22 . In that study, type 2 diabetes mellitus was associated with neuropathy and a progressive loss of corneal nerve fibers.…”
supporting
confidence: 53%
“…55 Furthermore, in diabetic patients treated with CSII, there was evidence of corneal nerve regeneration, without an improvement in NCS over 24 months. 29 We have also shown corneal nerve regeneration in physically active patients with type 2 diabetes over 24 months, 56 whereas a recent meta-analysis showed no change in peroneal and sural NCV in patients who exercise. 57 In an early study, we showed corneal nerve regeneration after 24 months of improvement in HbA1c, lipids and blood pressure, 48 whilst in a recent study from Japan, a decrease in HbA1c and weight was associated with improved nerve conduction and corneal nerve regeneration over 4 years.…”
Section: Change At 1-5 Yearsmentioning
confidence: 88%
“…Despite NZ podiatrists advocating for the importance of physical exercise and mobility, the results indicate that the education provided to patients around exercise is still largely based on the clinician’s individual experience. Exercise has been identified as potentially playing an important role as an intervention in the non-pharmacological treatment of DFD, including on the progression of diabetes-related peripheral neuropathy [ 31 ]. However, despite an increased number of studies investigating the provision of foot and mobility-related exercise as an intervention to prevent foot ulcers there continues to be a small research evidence base in this area [ 24 , 32 ].…”
Section: Discussionmentioning
confidence: 99%